Black Soldier Fly Full-Fat Larvae Meal as an Alternative to Fish Meal and Fish Oil in Siberian Sturgeon Nutrition: The Effects on Physical Properties of the Feed, Animal Growth Performance, and Feed Acceptance and Utilization - Rawski, Mateusz (Animals (Basel), 2020)
SIMPLE SUMMARY: Research for alternative protein sources that may replace fish meal and fish oil in fish diets is one of the ongoing tasks for aquaculture. Sturgeons role captive fish production increases due to the rapid decrease in its wild stocks during the 20th century. Insect meals are a novel group of feed materials rich in nutrients that are produced in an environmentally sustainable way. Therefore, the aim of the study was to assess the effects of black soldier fly larvae full-fat meal (BSFL) usage as fish meal and fish oil replacement in Siberian sturgeon diets. The experimentally obtained data showed the possibility of extruded feed production with up to 30% of BSFL and physical parameters suitable for fish feeding. Moreover, feed acceptance increase was observed in treatments containing than 10% and higher shares of BSFL. In the groups whose feed contained 5 to 30% of BSFL in the diet, the growth of experimental fish as well as their feed utilization parameters were improved; however, with no effects on feed digestibility. All presented data make BSFL a suitable nutrient source alternative to fish meal in Siberian sturgeon nutrition. ABSTRACT: This study provides data on the use of black soldier fly (Hermetia illucens) full-fat meal (BSFL) in Siberian sturgeon (Acipenser baerii) nutrition, examining pellet physical properties, growth performance, feed acceptance and utilization, apparent protein, and fat digestibility. The study consisted of: feed quality assessment; a growth performance; feed acceptance; digestibility trials. The effect of the use of BSFL as a replacement for fish meal (FM) and fish oil (FO) was investigated. The applied BSFL shares were 5%, 10%, 15%, 20%, 25%, and 30% of the diet, replacing up to 61.3% of FM and allowing us to reduce FO use by up to 95.4% in the case of 30% incorporation. The applied substitution affected feed quality, increasing the expansion rate, and decreasing feed density, sinking speed and water stability. However, body weight gain, specific growth rate, feed, and protein conversion ratios, were improved in groups fed BSFL. Moreover, feed acceptance was increased with treatments containing 10 to 30% BSFL. No effects on nutrients digestibility were observed. The results show that the use of BSFL as an FM and FO replacement may have positive effects on sturgeon growth performance, and BSFL can be developed as a promising alternative feed material.